A 2.8 Mb YAC contig in 11q12-q13 localizes candidate genes for atopy: Fc epsilon RI beta and CD20. - Stafford, A; Rider, S; Hopkin, J; Cookson, W; Monaco, A (1994)
An important locus for Atopy (familial asthma, hay fever and eczema) has been localized to the 11q12-q13 region with the minimum recombination fraction around the CD20 gene. We have constructed a 2.8 megabase (Mb) Yeast Artificial Chromosome (YAC) contig of the candidate region using 15 STSs. A total of seven genes have been mapped within this interval in the order cen-OSBP-TCN1-GIF-Fc epsilon RI beta-CD20-CD5-PGA-q(ter) and can be covered by a minimum of eight YAC clones. Contig integrity was assayed with fluorescence in-situ hybridization (FISH) and the mapping of YAC ends on somatic cell and radiation hybrid panels. A long range restriction map of the contig has been constructed to establish the order of and distance between loci. Two promising candidates for the atopy locus, the beta subunit of the high affinity immunoglobulin E receptor (Fc epsilon RI beta) and CD20, a molecule involved in B cell differentiation, have been placed within the contig.